Right Tail of the Unemployment Duration in the Czech Republic - Čabla, Adam (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The aim of the paper is to compare three different approaches to modelling the distribution with supposed heavy tail using data about unemployment duration in the Czech republic – two models of spliced distributions and model with dynamic weights. All three aproaches are based on the Pickands-Balkema-de Haan theorem and incorporate the parametric distribution of the body of the probability distribution and generalized Pareto distribution used for the modelling of the right tail. The data come from the Labour Force Survey from three distinct periods - before the last economic crisis, during it and during the recovery from the crisis. The paper shows the differences between the right tails of the three periods and discussion of the used methods
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 59-74
Keywords: Unemployment Duration; Labour Force Survey; Right Tail; Extreme ValueTheory; Spliced Models; Dynamic Weight Mixture Model